Regime shift of bacterial communities in lake ecosystems in the arid and semi-arid north-west of China: Evidence from the sedimentary archives - Yang Hu; Jian Cai; Jingjing Bai; Wenfang Zhang; Yi Gong; Xingyu Jiang; Xiangming Tang; Keqiang Shao; Jianying Chao; Guang Gao (Ecological Indicators)
Since the middle of the last century, China has experienced social-economic progress and climate transition, which have been strong triggers for the regime shift of lake ecosystem, threatening species coexistence, biodiversity and community persistence. Given the high vulnerability of ecosystems in arid and semi-arid north-west of China, anticipating their regime shifts can contribute to the development of effective interventions to maintain lake health. However, it is not known how and to what extent lake ecosystems have changed in this region. To fill this gap, we investigated the imprints in paleolimnological sedimental cores over the last 150 ∼ 200 years in shallow Lake Bosten and deep Lake Sayram. Results showed that anthropogenic heavy metals showed a sudden increase along the sediment cores. In Lake Bosten, bacterial diversity, niche differentiation, and species interactions exhibited a stepwise shift from an alternative state to anther in a nonlinear manner, highlighting the existence of regime shift. In contrast, in Lake Sayram, the change in bacterial communities was more gradual. Compared with the two alternative states, network topology analysis revealed tighter bacterial interactions in the intermediate transitional phase, which implicates stable-unstable-stable progresses during the regime shift. Concurrently, the predominant deterministic processes in the two alternative states and stochastic processes in the transitional phase may reflect the important roles of stochasticity in triggering the regime shift. Overall, our study showed that anthropogenic activities lead to a regime shift in the shallow lake rather but not in the deep lake.